2022
DOI: 10.1155/2022/8227930
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence Mechanism of BIM on Green Building Engineering Project Management under the Background of Big Data

Abstract: The main framework of green construction management based on building information modeling (BIM) is constructed, and the related theories of BIM and green buildings are researched in more detail. The index of green construction is evaluated using the fuzzy evaluation method. The technical measures, management methods, field experience, and evaluation methods included in the green construction process are introduced in detail. Finally, effective measures to promote green construction management in China are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In procurement management, the most recurrent example of the use of these technologies is the use of artificial intelligence to automate processes, from quotation management to supplier selection and purchasing. Authoring is also currently supported by emerging technologies [8,62,74,83]. Stakeholders, communications, and human resources are less involved, focusing on process optimization in these areas, as well as the best practices for presenting results to stakeholders [9,55,92].…”
Section: Question 2-what Are the Most-used Methodological Routes And ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In procurement management, the most recurrent example of the use of these technologies is the use of artificial intelligence to automate processes, from quotation management to supplier selection and purchasing. Authoring is also currently supported by emerging technologies [8,62,74,83]. Stakeholders, communications, and human resources are less involved, focusing on process optimization in these areas, as well as the best practices for presenting results to stakeholders [9,55,92].…”
Section: Question 2-what Are the Most-used Methodological Routes And ...mentioning
confidence: 99%
“…In the records selected for this review, there are experiences where using data science makes it possible to optimize purchasing decisions, strategic preferences, cost management, and financial modeling [56,84]. Data science is also considered for constructive analysis (optimization) and sustainable (green) construction articulated with BIM [54,83].…”
Section: Question 1-what Are the Technologies Most Used In The Articl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Provide strong support. This integration not only brings benefits to the design and construction process [20], but also continues to play a role in the operation and maintenance phase of the building, laying a solid foundation for more environmentally friendly and efficient construction projects. At the same time, the comprehensive sharing and integration of information can be realized [11], so as to achieve the sustainability and greening goals of each stage of the construction project.…”
Section: Integration Of Green Building Materials and Bimmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%